2020
DOI: 10.1007/s40820-020-00472-8
|View full text |Cite
|
Sign up to set email alerts
|

One Stone Four Birds: A Novel Liposomal Delivery System Multi-functionalized with Ginsenoside Rh2 for Tumor Targeting Therapy

Abstract: Liposomes hold great potential in anti-cancer drug delivery and the targeting treatment of tumors. However, the clinical therapeutic efficacy of liposomes is still limited by the complexity of tumor microenvironment (TME) and the insufficient accumulation in tumor sites. Meanwhile, the application of cholesterol and polyethylene glycol (PEG), which are usually used to prolong the blood circulation and stabilize the structure of liposomes respectively, has been questioned due to various disadvantages. Herein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 48 publications
(61 reference statements)
1
72
0
Order By: Relevance
“…Chao et al reported that, compared with non-PEGylated liposomes, PEGylated liposomes adsorbed less proteins in the blood, which mainly reduced the affinity of immunoglobulins. However, apolipoprotein E, which has been shown to retard the phagocytosis of macrophages, was not found in the protein corona of PEGylated liposomes [ 66 ]. In our work, the protein compositions in the RBCm and the blood-treated nanocarriers (LCNPs and HA&RBCm-LCNPs) were quite different (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chao et al reported that, compared with non-PEGylated liposomes, PEGylated liposomes adsorbed less proteins in the blood, which mainly reduced the affinity of immunoglobulins. However, apolipoprotein E, which has been shown to retard the phagocytosis of macrophages, was not found in the protein corona of PEGylated liposomes [ 66 ]. In our work, the protein compositions in the RBCm and the blood-treated nanocarriers (LCNPs and HA&RBCm-LCNPs) were quite different (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the prolonged circulation of HA&RBCm-LCNPs in the blood is considered to have been achieved via the following: (1) alterations to the types rather than the amounts of proteins attached to the surface of the nanoparticles; (2) an abundance of CD47 and reduced affinity to myosins; and (3) excellent sustained-release properties. In addition, apolipoprotein E was detected in both LCNP and HA&RBCm-LCNP groups ( p > 0.05), suggesting that the circulatory properties of the tested nanocarriers are distinct from those of PEGylated nanoparticles [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the stealth effect of NPs modified with ginsenosides reduced the adsorption of opsonins on the surface of the liposomes. Ginsenosides Rh2, Rg3 and Rg5 have shown a stealth effect due to the increased adsorption of apolipoprotein E, which can retard the absorption of macrophages to liposomes [ 25 ].…”
Section: Ginsenosidesmentioning
confidence: 99%
“…Developing a new ginsenoside DDSs has attracted wide attention in attempts to achieve synergism and detoxification, as well as to improve bioavailability. Furthermore, because of the similar structure of cholesterol and ginsenosides, the latter have been used as excipients to synthesize liposomes with simultaneous targeting ability [ 25 28 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hong reported ginsenoside Rh2 could improve physical and chemical properties of phospholipid bilayer. 29 But the aforementioned compounds are triterpenoid pentacyclic saponin. The interaction of steroid pentacyclic saponin with lipid membranes remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%